Edukasi Tentang Pentingnya Deteksi Dini Anemia Dan Pengaturan Pola Makan Pada Ibu Hamil - nurul, waodenurulmutia (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The aim of this service is to increase participation and awareness of pregnant women in implementing a balanced diet as an effort to prevent anemia. The activity method uses these steps: 1) The respondent meeting on the first day was a meeting attended by 25 pregnant women. 2) Carry out a pre-test for all pregnant women before starting to deliver anemia material. 3) Delivery of material and education about anemia in pregnancy. 4) A post test is carried out regarding anemia during pregnancy presented by the speaker. The results of the activity show that 1). Pregnant women with anemia in the Meo-Meo health center work area do not know in depth about the importance of early detection and maintaining diet during pregnancy. 2). It is known that there is an increase in pregnant women's knowledge about the importance of diet and early detection of anemia in pregnancy before and after attending health education in the form of lectures and group discussions.